Analysis of Supreme Court Regulation Number 1 of 2020 Concerning Guidelines for The Criminalization of Corruption Crimes in the Perspective of Justice - Yoga, Yoga Wiranata; Dinata, M Ruhly Kesuma (Future Science / FSH-PH Publications, 2025)
Supreme Court Regulation (Perma) Number 1 of 2020 was issued as a guideline for judges in determining the punishment of perpetrators of corruption crimes. This guideline aims to create legal certainty, pro-portionality, and consistency in the imposition of criminal sanctions in order to achieve substantive justice. This study analyzes the extent to which the application of the Perma has reflected the principle of justice, both from the perspective of criminal law and restorative jus-tice. Using juridical-normative methods and a case comparison ap-proach, this study finds that the implementation of Perma No. 1 of 2020 still faces challenges in judicial practice, especially in adjusting to the elements of state losses and the level of guilt of the defendants. The problem that will be discussed in this study is how urgent is the evaluation of Perma No. 1 of 2020 concerning guidelines for criminal-izing corruption crimes from a justice perspective. The research method used is a normative research method with a statute ap-proach, case approach, and theoretical approach, and analyzed using content analysis.